2019
DOI: 10.1186/s12896-019-0564-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for in vitro preparation of natural killer cells from cord blood

Abstract: BackgroundCord Blood (CB) has been considered a promising source of natural killer (NK) cells for cellular immunotherapy. However, it is difficult to expand the large numbers of highly pure NK cells from CB without cell sorting and feeder cells/multiple cytokines. In this study, we try to develop a simple, safe and economical method for ex vivo expansion and purification of NK cells from CB without cell sorting and feeder cells/multiple cytokines.ResultsThe large numbers (mean: 1.59 × 1010) of highly pure (≥90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
18
0
2
Order By: Relevance
“…Typically, a dose of UCB or placenta donor can be expended to an amount sufficient for one adoptive transfer procedure. For instance, 21-day NK culture of placenta-isolated NKs yields an average of 1.2 × 10 9 NK cells with around 80% viability [ 106 ] and 1.59 × 10 10 NK cells with an average purity of 92.37% from UCB [ 107 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, a dose of UCB or placenta donor can be expended to an amount sufficient for one adoptive transfer procedure. For instance, 21-day NK culture of placenta-isolated NKs yields an average of 1.2 × 10 9 NK cells with around 80% viability [ 106 ] and 1.59 × 10 10 NK cells with an average purity of 92.37% from UCB [ 107 ].…”
Section: Main Textmentioning
confidence: 99%
“…A more simplified NK cell expansion method has been used by combining group A streptococcus and zoledronate with IL-2 to stimulate UCB-derived mononuclear cells. This method resulted in a 1,560-fold expansion of NK cells with a purity of 92.37% after 21 days of ex vivo culture [ 107 ]. This method was advantageous in that it did not require magnetic cell sorting, feeder cells, or multiple cytokines, potentially lowering the cost of production.…”
Section: Main Textmentioning
confidence: 99%
“…IL-15 outperformed IL-2 in this setting for NK cell purity, and a GMP-compliant process is being evaluated in a phase 1 trial treating refractory lymphoma and myeloma in combination with monoclonal antibody therapy, delivering up to 2 £ 10 8 cells/kg [70]. A recent report describes the use of IL-2, zoledronate (a Food and Drug Administration-approved bisphosphonate medication used in the treatment of osteoporosis and bony metastases) and a group A streptococcus preparation as an activating cocktail, resulting in NK expansion from UCB to numbers suitable for clinical use [71]. Zoledronate and group A streptococcus displayed synergistic benefits with regard to the degree and purity (>90%) of NK cell expansion.…”
Section: Feeder-free Nk Cell Expansionmentioning
confidence: 99%
“…To date, various protocols have been employed for ex vivo expansion and differentiation of NK cells from HSC sources; however, there are still several technical hindrances despite using different combinations of cytokines with or without feeder cell lines, and the use of animal and human sera could lead to many It has been shown that the expanded CD34 + cells could be differentiated into a NK cell product with an average purity of 40-60% after 5-7 weeks of culture (Kao et al, 2007;Mu et al, 2019;Spanholtz et al, 2011). Many studies have reached a calculated mean expansion rate of 300-fold during the NK cell generation phase (Spanholtz et al, 2011;Spanholtz et al, 2010).…”
Section: -B-c and 3-a)mentioning
confidence: 99%